Lichen Sclerosus Atrophicus [LSA] in the Areolae: A Case Report - L. Padmavathy; L. Lakshmana Rao; M. Dhana Lakshmi; N. Sylvester; N. Ethirajan (Hindawi Limited, 2012)
Lichen sclerosus (LS) is a chronic inflammatory disorder of an unknown aetiology most commonly affecting the anogenital area. However, extragenital involvement also occurs uncommonly. A case of extra-genital LS involving the areolae of both breasts, in a 15-year-old boy, is reported for its rarity.